(untitled) (Journal of Dhaka Medical College, 2016)
Objective: Olfactory Groove Meningioma(OGM) are rare benign tumour account for 8-13% of all intracranial meningiomas and reported about 12 % of all basal meningiomas. Anosmia is thought to be among the commonest symptoms, even though patients often present with headache, visual problem and mental dysfunction. Methods: Tweenty patients (male = 12 andfemale = 8) with olfactory groove meningioma were examined. In all patients extensive pre operative and post operative olfactory testing was performed using conventional soap and cotton soaked with perfume. In 14 cases, meningioma was lateralized (8 Left, 6 Right), in 6 patients meningioma were extended in both sides. CT and MRI scans were performed in all cases. Results:In preoperative testing, 14 patients were found to be anosmic on the side of the tumor, 2 were hyposmic and 4 were normosmic. Postoperative ipsilaterally all patients became anosmic but contralaterally 14 patients were anosmic ,2 were hyposmic and 4 were normosmic. Conclusion:The likelihood of normal post operative olfactory function preservation contra lateral to the tumour was possible in too some extent in smaller size.However,preservation of olfactory function ipsilateral to the tumor seems to be extremely difficult irrespective of tumor size or surgical approach. J Dhaka Medical College, Vol. 24, No.1, April, 2015, Page 44-46